Inclusive Governance and Service Delivery: Public Sector Innovation through the JEBOL Program in Indonesia’s Civil Registration System - Sidiyani, Ni Komang Ayu Sri; Prabawati, Ni Putu Anik (Universitas Pattimura, 2025)
This study analyzes the effectiveness of public service innovation through the Jemput Bola (JEBOL) program in the electronic ID card (KTP-el) registration system at the Population and Civil Registration Office of Badung Regency, Indonesia. JEBOL was developed in response to the public demand for more accessible and inclusive administrative services, especially for residents in remote areas or with limited mobility. Using a descriptive qualitative approach, data were collected through in-depth interviews, field observations, and documentation. Findings show that the JEBOL program has improved accessibility and coverage of KTP-el registration services and has been well-received by the community. Nevertheless, challenges remain in document verification processes, limited human resources, and transportation infrastructure. While the program has proven effective in expediting KTP-el services, it has yet to comprehensively address other administrative needs. The novelty of this study lies in its inclusive governance approach to public service innovation, emphasizing grassroots engagement and collaboration with local actors. The study recommends optimizing digital technology use, enhancing community outreach, and strengthening partnerships between local governments and village administrations to ensure the program’s sustainability and scalability. These findings contribute to public service governance, social innovation, and community-based policy studies within the broader social sciences and humanities discourse.